2002
DOI: 10.1007/s11746-002-0444-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of free and esterified sterols in vegetable oils

Abstract: sterols were separated by silica gel column chromatography upon elution with n-hexane/ethyl acetate (90:10 vol/vol) followed by n-hexane/diethyl ether/ethanol (25:25:50 by vol). Both fractions were saponified separately and the phytosterol content was quantified by GC. The analytical method for the analysis of esterified and free sterols had a relative standard deviation of 1.16% and an accuracy of 93.6-94.1%, which was comparable to the reference method for the total sterol analysis. A large variation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
93
4
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(113 citation statements)
references
References 22 publications
13
93
4
3
Order By: Relevance
“…Phytosterol content and composition changes during the hole refining process were evaluated by Verleyen, Forcades et al (2002) who found that the process modified the phytosterol composition by increasing the esterified sterols passing from 28.6% in bleached oil to 40% in the refined oil (after the deodorization) of the total sterol content. Karaali (1985) determined in chemically refined sunflower oil a decrease of 60.3% on total phytosterols, with the highest loss during the physical neutralization step.…”
Section: Refined Vs Crude Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytosterol content and composition changes during the hole refining process were evaluated by Verleyen, Forcades et al (2002) who found that the process modified the phytosterol composition by increasing the esterified sterols passing from 28.6% in bleached oil to 40% in the refined oil (after the deodorization) of the total sterol content. Karaali (1985) determined in chemically refined sunflower oil a decrease of 60.3% on total phytosterols, with the highest loss during the physical neutralization step.…”
Section: Refined Vs Crude Oilmentioning
confidence: 99%
“…A significant decline in the total sterol content in vegetable oil has been reported during the chemical neutralization step (Gutfinger and Letan, 1974), which is attributed to a liquid-liquid partitioning of phytosterols into the soapstock (Serani and Piacenti, 1992 (Alpaslan et al, 2001;Ergönül and Köseoǧlu, 2014;Karaali, 1985;Kreps et al, 2014;Nergiz and Çelikkale, 2011;Talal et al, 2013;Tasan and Demirci, 2005;Verleyen, Forcades et al, 2002).…”
Section: Neutralizationmentioning
confidence: 99%
“…Such a supplementation was more than sufficient to satisfy the requirements for S. serrata [21], which is an essential nutrient for crustaceans due to their inability to synthesize this de novo [29]. Another possible contributor to the reduced whole-body cholesterol was due the presence of phytosterols, which can diminish cholesterol absorption [30], and the tested vegetable oils in the current study are also known to contain this compound [31]. In addition, it may be possible that cholesterol transport via lipoproteins was disrupted as suggested by Noordin et al [2].…”
Section: Discussionmentioning
confidence: 74%
“…The most important sterol present in vegetable oils is -sitosterol, a desmethyl sterol, which accounts for 38 to 95% of the total phytosterols available in various oils (Verleyen et al, 2002) whereas mono and di-methyl sterols are found in lower amount in these oils (Johansson et al, 1979;Chryssafidis et al, 1992;Eldin and Appelqvist, 1994) but certain oils such as olive and linseed oil contain substantial amounts of dimethyl sterols (Johansson 1979). Distribution of phytosterols to free sterols and steryl fatty acid esters account for different proportion in different oils (Johansson et al, 1979;Ferrari et al, 1996;Verleyen et al, 2002;Phillips et al, 2002;Worthington and Hitchcock, 1984;Gordon and Griffith, 1992) for example-free sterols accounts for nearly 54-85% of total phytosterols in soybean, sesame, olive, cotton seed, coconut, safflower, and peanut oil whereas the proportion varies for 32-44% in canola, rapeseed, corn, avocado and sunflower oil (Phillips et al, 2002).…”
Section: Sitosterol Brassicasterolmentioning
confidence: 99%